Evaluation of the Mechanical Properties of bolted connections with extended endplate by EN 1993-1-8:2005 and ABNT NBR 8800:2008 (Research, Society and Development, 2021)
This paper concerns the study of the semi-rigid behavior of bolted beam-column connections with extended endplate and transverse stiffeners in the column web based on the Component Method presented in EN 1993-1-8:2005. The moment x rotation relationship of such connections with different endplate thicknesses are obtained according to the Brazilian and European standards, from where the related resistance values are determined. It is observed that all connection designs with the Brazilian standard have a lower resistance to bending moment if compared to the European standard designs, getting worse as the thickness of the endplate decreases. Finally, it is concluded that it may be incorrect not to associate the concept of semi-rigid behavior to connections with transversely stiffened endplates, since the behavior of such connections can be quite different from an ideally rigid connection assumption.